Criminal Act of Corruption Abuse of Authority Of Office (Analysis of Decree No.16 Pid.Sus-Tpk/2018/Pn.Jkt.Pst) - Dedi Pulungan; Boy Nurdin; Faisal Santiago (Publikasiku, 2023)
Corruption in government bodies carried out by bureaucratic machines that are seen is only corruption with a state loss of more than 1 (one) billion, while below one billion is rarely found, because the focus of eradicating corruption is indeed worth 1 billion and above and mostly involves